EFEK DOKSISIKLIN SELAMA MASA ORGANOGENESIS PADA STRUKTUR HISTOLOGI ORGAN HATI DAN GINJAL FETUS MENCIT - Heri Budi Santoso; Anni Nurliani (Bioscientiae, 2006)
A study has been conducted to identify changes in histologic structure of liver and kidney of mice fetus from pregnant mother mice exposed to doxicycline during organogenesis period.  Twenty four 3 month old female mice were divided into 4 groups: control, and treatments with oral dose of doxicycline of 26 mg, 52 mg, and 104 mg/kg BW/day for 10 days, coincided with sixth day until fifteenth day of pregnancy. At the sixteenth day of pregnancy all mice were killed, the fetus were taken for liver and kidney histologic slides.  From each histologic slide 6 samples were inspected under light microscope.  Changes in histologic structure of liver mice fetus included necrosis of liver cell; the kidney showed degeneration of epitel cell kidney tubulous begin 52 mg/kg BW dose.